Acetic acid treated Pt and Ti doped alpha-Fe2O3 film electrode as well as preparation method and application thereof
The Pt and Ti doped α-Fe2O3 film electrodes by acetic acid are solved, and the existing photoelectric catalytic preparation of hydrogen peroxide is achieved, which is efficient and stable hydrogen peroxide synthesis, meeting the requirements of green chemistry.
Patent Information
- Application Number
- CN202411866468.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the method of photoelectro-catalyzed hydrogen peroxide is inefficient and costly, and it is difficult to meet the requirements of green chemistry.
Acetic acid was used to treat Pt and Ti doped α-Fe2O3 thin film electrodes, and a photoelectrode with high efficiency catalytic activity was formed through the acetic acid solution so as to immerse and calcinate the acetic acid solution.
The efficiency of photoelectro-catalyzed water oxidation is improved, and the synthesis of hydrogen peroxide with high yield and high stability is achieved, and the process is simple and the raw materials are easy to obtain.
Smart Images

Figure CN119640322A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical catalysis, and in particular relates to an acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode and a preparation method and application thereof. Background Art
[0002] Hydrogen peroxide (H2O2) is a very important chemical, which is widely used in papermaking, textiles, wastewater treatment and other fields. At present, the method for preparing H2O2 in industry is the anthraquinone method. Although this technology is safe, reliable and efficient. However, this technology has high production cost, unsafe transportation process, and easy pollution of production process, which is not conducive to the requirements of green chemistry at this stage. Developing a method that is simple, cheap, environmentally friendly and can produce H2O2 at any time is an effective way to replace the anthraquinone method. Since Fujishima and Honda used TiO2 photoanode to realize photoelectrocatalytic (PEC) water decomposition to produce hydrogen in 1972 (Fujishima, A., Honda, K.; Electrochemical photolysis of water at a semiconductor electrode. Nature 1972, 238, 37-38.), the development of photoelectrochemical water decomposition technology has made great progress. Using solar energy to synthesize H2O2 is an effective way to realize solar energy to chemical energy. In the process of photoelectric synthesis of H2O2, one method is to prepare H2O2 by oxygen reduction at the photocathode and produce O2 at the photoanode. Another more ideal process is to synthesize H2O2 by water oxidation at the anode and produce hydrogen at the photocathode.
[0003] The electrode potential required for the photoanode to synthesize H2O2 is 1.76V (vs. RHE). This higher electrode potential has more stringent requirements on the band gap and energy band of the semiconductor. At present, research on the preparation of H2O2 by photoelectrocatalytic photoanode is in its initial stage. This method can produce H2O2 in a controllable manner, and the H2O2 produced in situ can be used for the degradation of some environmental pollutants, solving a series of problems such as the synthesis and transportation of H2O2. Chinese invention patent CN110468428B reports "a semiconductor anode material for photoelectrocatalytic preparation of hydrogen peroxide and its preparation method". The semiconductor used in this patent is TiO2. TiO2 is a semiconductor that responds to ultraviolet and visible light, resulting in the Faraday efficiency of this photoelectrode being only 23.3%. Chinese invention patent CN111979561A reports "SnO x / BiVO4 electrode, preparation method thereof and application in photoelectrocatalytic hydrogen peroxide synthesis". The semiconductor used in this invention is BiVO4. Although it has visible light activity, its synthesis raw materials are expensive and involve some processes such as spin coating, which limits the economic use of the catalyst.
[0004] Therefore, how to provide an efficient and inexpensive anode material for photoelectrically producing hydrogen peroxide is a technical problem that those skilled in the art need to solve urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes an acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode and a preparation method and application thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing an acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode comprises the following steps:
[0008] The Ti / Pt:Fe2O3 electrode is immersed in an acetic acid solution and then calcined to obtain a HAc-Ti / Pt:Fe2O3 thin film electrode.
[0009] Beneficial effects: In terms of photoelectrocatalytic water oxidation, the doping of Pt and Ti in the present invention promotes the separation of photogenerated carriers, and the presence of acetate ions forms oxygen vacancies on the catalyst surface, which helps to promote the separation and migration of charges, thereby improving the photoelectrocatalytic efficiency.
[0010] Preferably, the mass fraction of the acetic acid is 98%.
[0011] Beneficial effects: The use of 98% acetic acid solution can promote the generation of oxygen vacancies on the surface of the photoelectrode, promote the separation and migration of charges, and thus improve the catalytic efficiency of the electrode.
[0012] Preferably, the soaking temperature is room temperature and the soaking time is 5 minutes;
[0013] The calcination temperature is 450° C. and the calcination time is 30 min.
[0014] Beneficial effect: Under the above immersion conditions, suitable oxygen vacancies can be generated on the catalyst surface.
[0015] Preferably, the preparation method of the Ti / Pt:Fe2O3 electrode comprises the following steps:
[0016] After FeCl3·6H2O, urea, TiCl3 solution and H2PtCl6 solution are mixed and dissolved in water, they are added into the matrix for hydrothermal reaction, and after the reaction is finished, they are washed and calcined to obtain the Ti / Pt:Fe2O3 electrode.
[0017] Beneficial effects: The present invention utilizes α-Fe2O3 electrode to form a high-performance composite material by combining titanium (Ti) and platinum (Pt). This composite material not only improves the catalytic activity of the electrode, but also enhances the stability of the electrode.
[0018] Preferably, the TiCl3 solution is purchased as analytically pure stock solution (the mass fraction of TiCl3 in a 30% HCl solution is 15.0% to 20%);
[0019] The concentration of the H2PtCl6 solution is 10 g / L;
[0020] The ratio of the added amounts of the FeCl3·6H2O, urea, TiCl3 solution and H2PtCl6 solution is 1.216 g: 0.541 g: 30 μL: 100 μL.
[0021] Beneficial effect: By precisely controlling the concentration of TiCl3 and H2PtCl6 and the proportion of added amounts, the uniform distribution and good combination of Pt and Ti in α-Fe2O3 on the electrode can be ensured.
[0022] Preferably, the substrate is FTO conductive glass.
[0023] Beneficial effects: The present invention selects FTO conductive glass as the substrate of the Ti / Pt:Fe2O3 electrode, which improves the photoelectric performance and stability of the electrode and facilitates the preparation and processing of the electrode.
[0024] Preferably, the temperature of the hydrothermal reaction is 100° C. and the time is 6 hours.
[0025] Beneficial effect: The present invention is conducive to forming a more uniform and dense electrode structure of Pt on Ti on FTO under hydrothermal conditions of 100°C.
[0026] Preferably, the calcination is: first calcining at 550° C. for 2 hours, then heating to 650° C. for 15 minutes.
[0027] Beneficial effect: The present invention adopts a calcination process of first calcining at 550°C for 2 hours and then heating to 650°C for 15 minutes, which not only optimizes the crystal structure and material properties of the electrode, but also improves the stability and durability of the electrode.
[0028] An acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode prepared by the above preparation method.
[0029] The invention discloses an acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode and its application in photoelectrocatalytic preparation of hydrogen peroxide.
[0030] A method for preparing H2O2 by photoelectrocatalytic photoanodic water oxidation, using a three-electrode system, and evaluating the performance of photoelectrocatalytic water oxidation to synthesize hydrogen peroxide in an H-type electrolytic cell;
[0031] The H electrolytic cell uses the HAc-Ti / Pt:Fe2O3 thin film electrode as the working electrode, the Pt sheet as the counter electrode, the Ag / AgCl as the reference electrode, the anolyte is 1M KHCO3, the catholyte is 0.2M Na2SO4, and the proton exchange membrane is 117.
[0032] Beneficial effects: The HAc-Ti / Pt:Fe2O3 of the present invention has sunlight responsiveness and is used as a photoanode material for photoelectrocatalytic synthesis of H2O2. The valence band position of the HAc-Ti / Pt:Fe2O3 thin film electrode obtained by the present invention is 2.4V (vs.RHE), which meets the electrode potential (1.76V vs.RHE) for water oxidation synthesis of H2O2. The doping of Pt and Ti promotes the carrier separation ability of the α-Fe2O3 electrode. After HAc treatment, more oxygen vacancies are formed on the surface of the Ti / Pt:Fe2O3 electrode. The surface states formed by these oxygen vacancies further promote the carrier separation ability of the electrode, so that the HAc-Ti / Pt:Fe2O3 electrode has good performance in photoelectrocatalytic water oxidation synthesis of hydrogen peroxide. In addition, the H2O2 generated in situ by photoelectrocatalysis in the present invention can be used for the degradation of the environmental pollutant methyl orange.
[0033] Compared with the prior art, the present invention has the following advantages and technical effects:
[0034] The present invention synthesizes a HAc-Ti / Pt:Fe2O3 photoelectrode with visible light absorption effect, and for the first time uses the HAc-Ti / Pt:Fe2O3 photoelectrode material for photoelectric water oxidation to prepare H2O2. The electrode has the characteristics of high H2O2 production and high stability. In addition, the preparation method provided by the present invention is simple, and the raw materials are easily available, which is convenient for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0036] Figure 1 This is a SEM image of the HAc-Ti / Pt:Fe2O3 thin film electrode obtained in Example 1 of the present invention; wherein a is α-Fe2O3; b is HAc-Ti / Pt:Fe2O3;
[0037] Figure 2 TEM image of the HAc-Ti / Pt:Fe2O3 thin film electrode obtained in Example 1 of the present invention; wherein a is α-Fe2O3; b is HAc-Ti / Pt:Fe2O3;
[0038] Figure 3XRD diagrams of the α-iron oxide thin film electrode and the HAc-Ti / Pt:Fe2O3 thin film electrode obtained in Example 1 of the present invention;
[0039] Figure 4 The XPS graphs of HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 obtained in Example 1 of the present invention;
[0040] Figure 5 The EPR images of HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 obtained in Example 1 of the present invention are shown in FIG.
[0041] Figure 6 The current density diagram of HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 obtained in Example 1 of the present invention in 1MKHCO3 (pH=8.6) under xenon lamp irradiation;
[0042] Figure 7 The standard curve diagram of the H2O2 detection method obtained in Example 1 of the present invention; a is the absorption spectrum diagram, and b is the standard curve;
[0043] Figure 8 The amount of hydrogen peroxide synthesized by HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 at a voltage of 1.7V (vs.RHE) obtained in Example 1 of the present invention;
[0044] Fig. 9 The stability of the thin film electrodes of HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 obtained in Example 1 of the present invention at a voltage of 1.23V (vs.RHE);
[0045] Fig.10 This is a performance diagram of HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 obtained in Example 1 of the present invention for degrading methyl orange. DETAILED DESCRIPTION
[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0048] The embodiment of the present invention discloses a method for preparing a Pt, Ti-doped α-Fe2O3 thin film electrode treated with acetic acid, comprising the following steps:
[0049] The Ti / Pt:Fe2O3 electrode is immersed in an acetic acid solution and then calcined to obtain a HAc-Ti / Pt:Fe2O3 thin film electrode.
[0050] In a preferred embodiment, the mass fraction of the acetic acid solution is 98%. If the concentration is lower than this, its acidity will be weakened and the chemical reaction with the electrode surface will not be sufficient.
[0051] In a preferred embodiment, the soaking temperature is room temperature and the soaking time is 5 minutes;
[0052] The calcination temperature is 450°C and the calcination time is 30 minutes. If the temperature is lower than this, the electrode crystallinity will be insufficient, the active sites will be reduced, and the performance will be reduced. If the temperature is higher than this, the FTO will melt at high temperature.
[0053] In a preferred embodiment, the method for preparing the Ti / Pt:Fe2O3 electrode comprises the following steps:
[0054] After FeCl3·6H2O, urea, TiCl3 solution and H2PtCl6 solution are mixed and dissolved in water, they are added into the matrix for hydrothermal reaction, and after the reaction is finished, they are washed and calcined to obtain the Ti / Pt:Fe2O3 electrode.
[0055] In a preferred embodiment, the TiCl3 solution is a purchased analytically pure stock solution (the content of TiCl3 in a 30% HCl solution is 15.0% to 20%);
[0056] The concentration of the H2PtCl6 solution is 10 g / L. If the concentration is lower than this, insufficient Pt content, reduced catalytic activity and decreased electrode performance will result. If the concentration is higher than this, Pt particles will agglomerate, resources will be wasted and the electrode structure will be affected.
[0057] In a preferred embodiment, the ratio of the amount of FeCl3·6H2O, urea, TiCl3 solution and H2PtCl6 solution added is 1.216g: 0.541g: 30μL: 100μL. Under this ratio, a high-performance composite material is formed. This composite material not only improves the conductivity and catalytic activity of the electrode, but also enhances the stability and durability of the electrode;
[0058] In a preferred embodiment, the substrate is FTO conductive glass.
[0059] In a preferred embodiment, the temperature of the hydrothermal reaction is 100°C and the time is 6 hours. If the temperature is higher than this, the reaction will be too violent and difficult to control, and the crystal structure of the synthesized FeOOH may change, such as abnormal growth or phase change of the grains, thereby affecting the catalytic performance of the electrode. If the temperature is lower than this condition, the FeOOH crystals may not grow fully, resulting in an increase in crystal defects and uneven crystal size, thereby affecting the catalytic activity and stability of the electrode.
[0060] In a preferred embodiment, the calcination is: first calcining at 550°C for 2h, then heating to 650°C for 15min. The present invention adopts a two-calcination method, first removing volatile substances and initial crystallization at 550°C, and then further improving the crystal structure at 650°C to promote the stability of the Ti / Pt:Fe2O3 electrode.
[0061] The embodiment of the present invention also discloses an acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode prepared by the above preparation method.
[0062] The embodiment of the present invention also discloses the use of an acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode in photoelectrocatalytic preparation of hydrogen peroxide.
[0063] The embodiment of the present invention also discloses a method for preparing H2O2 by photoelectrocatalytic photoanodic water oxidation, using the HAc-Ti / Pt:Fe2O3 thin film electrode as the working electrode, the Pt sheet as the counter electrode, Ag / AgCl as the reference electrode, the anode electrolyte being 1M KHCO3, and the cathode electrolyte being 0.2M Na2SO4.
[0064] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0065] Among them, 1.216g of FeCl3·6H2O and 0.541g of urea were mixed and dissolved in 30mL of water, and FTO was added for hydrothermal reaction. After the reaction was completed, the α-Fe2O3 electrode was obtained by washing and calcining.
[0066] TiCl3 solution is a commercially available product, and its specific specifications are as follows: in a 30% HCl solution, the mass fraction of TiCl3 is 15.0% to 20%.
[0067] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0068] Example 1
[0069] A method for preparing a HAc-Ti / Pt:Fe2O3 thin film electrode comprises the following steps:
[0070] (1) Set the area to 1*2cm 2 The FTO conductive glass sheet was placed in acetone, ethanol and distilled water for ultrasonic cleaning for 30 minutes, with the power of the ultrasonic machine being 40MHz. Through further optimization, half of the area was covered with tape, and its actual area was determined to be 1*1cm 2 .
[0071] (2) 1.216 g of FeCl3·6H2O, 0.541 g of urea, 30 μL of TiCl3 solution and 100 μL of H2PtCl6 (10 g / L) solution were mixed and dissolved in 30 mL of distilled water to obtain a mixed solution.
[0072] (3) The mixed solution of step (2) was transferred to a reactor, and the FTO conductive glass was placed obliquely in the reactor in a "V" shape, and then the reactor was placed in an electric heating blast drying oven for hydrothermal reaction at a temperature of 100°C for 6 hours. After the reaction was completed, the film on the FTO conductive glass was washed with distilled water and naturally air-dried, and then calcined at 550°C in a muffle furnace for 2 hours, and then the temperature was raised to 650°C and calcined for 15 minutes to obtain a Ti / Pt:Fe2O3 electrode.
[0073] (4) 20 mL of acetic acid (mass fraction 98%) was measured and placed in a beaker, and then the Ti / Pt:Fe2O3 electrode obtained in step (3) was immersed in acetic acid for 5 minutes and then dried. Then, the obtained catalyst was calcined at 450°C in a muffle furnace for 30 minutes and then cooled to room temperature to obtain a HAc-Ti / Pt:Fe2O3 thin film electrode.
[0074] Figure 1 is the SEM image of the above HAc-Ti / Pt:Fe2O3 and α-Fe2O3, where: Figure 1 Where a is α-Fe2O3; b is HAc-Ti / Pt:Fe2O3. Figure 1 It can be seen that the morphology of the α-Fe2O3 thin film electrode treated with acetic acid and doped with Ti and Pt is consistent with that of α-Fe2O3, indicating that doping and acid treatment did not change the morphology of α-Fe2O3.
[0075] Figure 2 TEM images of the above-mentioned HAc-Ti / Pt:Fe2O3 and α-Fe2O3; Figure 2 As can be seen in part a, the lattice fringe is 0.221nm, corresponding to the (113) crystal plane of α-Fe2O3. Figure 2As can be seen from part b, the lattice fringes of the HAc-Ti / Pt:Fe2O3 thin film electrode obtained after acetic acid treatment are 0.229nm, corresponding to the (006) crystal plane of Fe2O3, indicating that the HAc treatment does not change the lattice of the HAc-Ti / Pt:Fe2O3 electrode.
[0076] Figure 3 The XRD patterns of the above-mentioned HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 thin film electrodes; the diffraction peaks of the photoanode after acid treatment and doping did not change the structure of α-Fe2O3.
[0077] Figure 4 The XPS graphs of the above-mentioned HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 thin film electrodes show that the elements Ti and Pt are uniformly doped in α-Fe2O3.
[0078] Figure 5 The EPR images of the above-mentioned HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 show that HAc-Ti / Pt:Fe2O3 has the largest oxygen vacancies, which is beneficial to the separation of charge carriers, making HAc-Ti / Pt:Fe2O3 have the best catalytic performance.
[0079] Comparative Example 1
[0080] A method for preparing a thin film electrode, which is different from Example 1 in that step (2) does not include H2PtCl6 solution and does not undergo acetic acid treatment, and the other process steps and parameters are the same as those of Example 1. Finally, a Ti:Fe2O3 thin film electrode is obtained.
[0081] Comparative Example 2
[0082] A method for preparing a thin film electrode is different from that of Example 1 in that step (2) does not include a TiCl3 solution and does not undergo acetic acid treatment, and other process steps and parameters are the same as those of Example 1. Finally, a Pt:Fe2O3 thin film electrode is obtained.
[0083] Application Example 1
[0084] The HAc-Ti / Pt:Fe2O3 thin film electrode, Ti / Pt:Fe2O3 thin film electrode, α-Fe2O3 thin film electrode obtained in Example 1, the Ti:Fe2O3 thin film electrode obtained in Comparative Example 1, and the Pt:Fe2O3 thin film electrode obtained in Comparative Example 2 were used as working electrodes, the Pt sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. Under the irradiation condition of the xenon lamp, the light source power was controlled to be 100 mW / cm 2In the H-type electrolytic cell, 1M potassium bicarbonate buffer solution was used as the anolyte, 0.2M Na2SO4 was used as the catholyte, and a 117-type proton exchange membrane was used in between. The three-electrode system was connected to an electrochemical workstation to test the various photoelectric properties of the electrodes.
[0085] Test results such as Figure 6 As shown, the results show that when under xenon lamp irradiation conditions simulating sunlight, the α-Fe2O3 film has a lower current, the current density of α-Fe2O3 (Ti / Pt:Fe2O3 electrode) is improved after Ti and Pt doping, and the Ti / Pt:α-Fe2O3 film electrode (i.e., HAc-Ti / Pt:Fe2O3 film electrode) treated with acetic acid has the highest current density at 1.76V (vs.RHE).
[0086] The DPD-POD method was used to detect hydrogen peroxide: prepare hydrogen peroxide solutions of different concentrations, take 2 mL of hydrogen peroxide solution, quickly add 0.4 mL of phosphate buffer solution, 3 mL of distilled water, 50 μL of N-N-diethyl-p-phenylenediamine (DPD) and 50 μL of peroxidase (POD) to the hydrogen peroxide solution in sequence, react for about one minute, and then detect the solution at an absorption wavelength of 551 nm. The obtained standard curve is as follows: Figure 7 shown.
[0087] According to the above method, the production of hydrogen peroxide was tested at 1.7 V (vs. RHE) for the synthesized HAc-Ti / Pt:Fe2O3, Ti / Pt:Fe2O3 and α-Fe2O3 electrodes. The results are as follows: Figure 8 As shown in the figure, it can be seen that HAc-Ti / Pt:Fe2O3 has the highest hydrogen peroxide yield among the three catalysts, which is 20.4 μmol h -1 cm -2 .
[0088] The stability of the electrode also has an important influence on the photoelectrode, such as Fig. 9 As shown, at a voltage of 1.23 V (vs. RHE), the HAc-Ti / Pt:Fe2O3 thin film electrode has good stability within a test time of 6 h.
[0089] The HAc-Ti / Pt:Fe2O3 thin film electrode, Ti / Pt:Fe2O3 and α-Fe2O3 thin film electrode obtained in Example 1 were used as working electrodes, the Pt sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. 2Under xenon lamp irradiation, the voltage was 1.23V (vs. RHE). In the H-type electrolytic cell, 20mg / L methyl orange solution was used as the anolyte, 0.2M Na2SO4 was used as the catholyte, and a 117-type proton exchange membrane was used in the middle. The three-electrode system was connected to the electrochemical workstation to test the degradation performance of the electrode. The results are shown in Fig.10 As shown, it can be seen that the HAc-Ti / Pt:Fe2O3 thin film electrode has the best methyl orange degradation efficiency.
[0090] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing an acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode, characterized in that: The following steps are involved: The Ti / Pt:Fe2O3 electrode is immersed in an acetic acid solution and then calcined to obtain a HAc-Ti / Pt:Fe2O3 thin film electrode.
2. The preparation method according to claim 1, characterized in that: The soaking temperature is room temperature and the soaking time is 5 minutes.
3. The preparation method according to claim 1, characterized in that: The calcination temperature is 450° C. and the calcination time is 30 min.
4. The preparation method according to claim 1, characterized in that: The preparation method of the Ti / Pt:Fe2O3 electrode comprises the following steps: After FeCl3·6H2O, urea, TiCl3 solution and H2PtCl6 solution are mixed and dissolved in water, they are added into the matrix for hydrothermal reaction, and after the reaction is finished, they are washed and calcined to obtain the Ti / Pt:Fe2O3 electrode.
5. The preparation method according to claim 4, characterized in that: The concentration of the H2PtCl6 solution is 10 g / L.
6. The preparation method according to claim 4 or 5, characterized in that: The ratio of the added amounts of the FeCl3·6H2O, urea, TiCl3 solution and H2PtCl6 solution is 1.216 g: 0.541 g: 30 μL: 100 μL.
7. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 100° C. and the time is 6 hours.
8. The preparation method according to claim 4, characterized in that: The calcination is as follows: first calcining at 550° C. for 2 h, then heating to 650° C. for 15 min.
9. The acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the acetic acid treated Pt, Ti doped α-Fe2O3 thin film electrode as claimed in claim 9 in photoelectrocatalytic preparation of hydrogen peroxide.
Citation Information
Patent Citations
A semiconductor anode material for photoelectrocatalytic preparation of hydrogen peroxide and its preparation method
CN110468428B
SnOx / BiVO4 electrode, preparation method thereof and application of SnOx / BiVO4 electrode to photoelectrocatalytic hydrogen peroxide synthesis
CN111979561A